A multiple-case assessment of product-service system leanness in UK manufacturing companies. (March 2016) - Elnadi, Moustafa; Shehab, Essam
Nowadays, manufacturing companies are moving towards lean practices and product-service system to develop their competitive ability. The purpose of this article is to present an innovative model to assess product-service system leanness incorporated with validating the model via three real-life case studies across various industries, thus improving the practical validity and relevance of the model. The model comprises three levels, namely, enablers, criteria and attributes. The first level contains five enablers, in the second level there are 21 criteria and finally the third level consists of 73 attributes. The development of the model was carried out through an iterative process. Starting from the literature review, going through semi-structured interviews with academic researchers involved in lean projects and ended with semi-structured interviews with a number of experts in the field of lean from five UK manufacturing companies. The model was validated by applying the model to compute the product-service system leanness level for three UK manufacturing companies and identifying areas for further improvement for these companies. The results indicate that the model is able to assess product-service system leanness level effectively and has a practical relevance.